Pewarisan Karakter Kuantitatif Persilangan Tanaman Melon - Badriyah Badriyah; Achmad Amzeri (Rekayasa, 2022)
One of the efforts to solve the problem of limited quality melon seeds is to assemble melon varieties with distinctive fruit characters in terms of shape, taste, and color of the flesh. In general, farmers choose meon seeds that have a sweet taste, flesh color, large fruit size, and have a long shelf life. Analysis of quantitative character inheritance is very important in plant breeding programs. This analysis is used to obtain genetic information consisting of the number of genes controlling the character, gene action, genetic diversity, heritability and other genetic information. This study aims to study the inheritance pattern of several quantitative characters in melon crosses. The research design was a randomized block design with eight genotypes as treatment. The results showed that there was a maternal effect on the two crosses of melon plants G1 ((PK-669 x D-612) and G3 ((PK-361 x PK-165) on the characters of fruit diameter, fruit length, fruit weight, and leaf area. Heritability values in a broad sense on all parameters ranged from 0.95-1.00.